Shoot Induction from Axillary Shoot Tip Explants of Fig (Ficus carica) cv. Japanese BTM 6 - Wan Ting Ling,; Fui Chu Liew,; Wei Yong Lim,; Sreeramanan Subramaniam,; Bee Lynn Chew, (Tropical Life Sciences Research, 2018)
Fig, or Ficus carica, is a fruit tree from the Moraceae family and is widely grown in tropical and subtropical regions of the world. Fig plants are mainly propagated through grafting, air layering, and hardwood cutting whereby these methods were found to be less efficient. Plant tissue culture is efficient method to propagate plants, particularly to produce true-to-type platelets for mass multiplication. The aim of this study is to induce multiple shoot formation on Ficus carica cv. Japanese BTM 6 through identifying and optimising the concentrations of 6-Benzylaminopurine (BAP) and Zeatin suited for shoot formation. The axillary shoot tip explants were cultured in MS media supplemented with different concentrations of BAP and Zeatin (0, 0.5, 1.0, 1.5 and 2.0 mg/L) to determine the optimal concentration for the formation of multiple shoots. Number of shoots per explants and the differences in shoot height of explants were calculated after 8 and 12 weeks of culture respectively. Of all the treatments of BAP, MS media containing with 2 mg/L BAP marked the highest number of shoots per explant with the average value of 1.67 ± 0.33 while 1.5 and 2 mg/L of BAP produced the highest differences in shoot height with 0.51 ± 0.08 cm and 0.51 ± 0.07 cm after 12 weeks respectively. Murashige and Skoog (MS) media supplemented with 2 mg/L Zeatin showed the highest production of multiple shoots and differences in shoot height with the average of 0.83 ± 0.219 and 0.32 ± 0.04 cm respectively among all the different treatments of Zeatin. In this study, BAP performed better in shoot induction and elongation as compared to Zeatin for the cultivar Japanese BTM 6. Pokok Tin, atau nama saintifiknya Ficus carica adalah pokok berbuah yang tergolong dalam famili Moraceae dan didapati di kawasan tropika dan subtropika dunia. Pokok Tin boleh dibiakkan dalam pelbagai teknik seperti cantuman, lenturan udara dan keratan kayu keras. Namun, kaedah-kaedah ini didapati kurang efisien. Kultur tisu tumbuhan merupakan satu kaedah yang cekap dalam pembiakan tumbuh-tumbuhan terutamanya dalam menghasilkan plantlet true-to-type. Tujuan kajian ini adalah untuk meningkatkan penggandaan pucuk Ficus carica dengan mengenal pasti dan mengoptimumkan penggunaan hormon 6-Benzylaminopurine (BAP) dan Zeatin yang sesuai untuk pertumbuhan pucuk. Eksplan pucuk aksilari telah dikultur secara berasingan pada kepekatan BAP dan Zeatin yang berbeza (0.0, 0.5, 1.0, 1.5 dan 2.0 mg/L) untuk menentukan kepekatan optimum bagi penggandaan pucuk. Penggandaan pucuk yang terhasil daripada pucuk eksplan dan purata panjang pucuk eksplan direkod selepas 8 dan 12 minggu. Antara semua rawatan dengan BAP, MS media yang mengandungi 2 mg/L BAP menghasilkan pucuk yang tertinggi dengan purata 1.67 ± 0.33 sementara 1.5 dan 2 mg/L BAP menghasilkan purata pucuk yang terpanjang dengan 0.51 ± 0.08 dan 0.51 ± 0.07. Rawatan 2 mg/L Zeatin menunjukkan penghasilan pucuk berganda yang paling banyak dan panjang di antara semua kepekatan Zeatin dengan purata 0.83 ± 0.219 dan 0.32 ± 0.04 cm serta merupakan rawatan yang terbaik untuk ketinggian tumbuhan. Kajian ini telah menunjukkan bahawa BAP menghasilkan penggandaan pucuk dan perbezaan ketinggian tumbuhan yang lebih baik daripada Zeatin untuk kultivar Japanese BTM 6.